Analisis Faktor-Faktor yang Mempengaruhi Keputusan UMKM dalam Memilih Pembiayaan Mudharabah di KSPPS Bina Syariah Ummah - Ayu Kharisma Wati; Moh. Ya’qub; Dwi Afriyanti (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
This study aims to analyze the factors influencing the decisions of Micro, Small, and Medium Enterprises (MSMEs) in Wadeng Village, Sidayu District, Gresik Regency, in choosing mudharabah financing at KSPPS Bina Syariah Ummah Wadeng Sidayu Gresik, East Java. The study also identifies the most dominant factor and examines the implications of mudharabah financing on the development of micro-enterprises in the area. This research employs a qualitative approach with a descriptive case study design. Primary data were collected through in-depth interviews, observations, and documentation involving MSME actors who are customers of mudharabah financing at KSPPS Bina Syariah Ummah. Secondary data were obtained from institutional documents, reports, and relevant literature. The findings reveal that MSMEs’ decisions to choose mudharabah financing are influenced by several factors, namely religiosity, business capital needs, ease of financing procedures, trust in the institution, service quality, and social environmental influences. The most dominant factor is religiosity, as the majority of MSME actors choose mudharabah financing to conduct their business activities in accordance with Islamic principles through a profit-sharing system that is perceived as more equitable. Furthermore, mudharabah financing contributes positively to business development by providing additional capital, enhancing business productivity, and supporting the sustainability of MSMEs.